2021
DOI: 10.5007/2175-7941.2021.e74782
|View full text |Cite
|
Sign up to set email alerts
|

A formação de professores na escola de Física do CERN: uma análise a partir dos focos da aprendizagem do professor pesquisador

Abstract: Este artigo trata da formação continuada de professores de Física de países lusófonos, no contexto da Escola de Física do Centro Europeu de Pesquisas Nucleares (CERN), realizada em parceria com pesquisadores e instituições de Portugal. Nossas principais inspirações teóricas e metodológicas foram os Focos da Aprendizagem do Professor Pesquisador (FAPP) e a Análise de Conteúdo (AC). Embasados em tais pressupostos, nosso objetivo principal foi evidenciar indícios de aprendizagem de um professor brasileiro partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…As identified by Costa et al (2021) the teachers participating in this research highlight emotional involvement and sensory experience as a striking element of technical visits. In this sense, the playful aspect of visitation can overlap with the scientific content related to the physical principles of operation of detectors and accelerators, for example.…”
Section: The Eso-exo Communicationmentioning
confidence: 89%
See 2 more Smart Citations
“…As identified by Costa et al (2021) the teachers participating in this research highlight emotional involvement and sensory experience as a striking element of technical visits. In this sense, the playful aspect of visitation can overlap with the scientific content related to the physical principles of operation of detectors and accelerators, for example.…”
Section: The Eso-exo Communicationmentioning
confidence: 89%
“…Thus, the broad context can make the teacher feel 'privileged' to participate in EF-CERN, which ends up reinforcing the commitment to the organization, carrying out, on return to Brazil, dissemination activities related to CERN. Costa et al (2021) also identified that teachers perceive themselves to be involved and responsible for multiplying their experience at CERN. Articulating Ludwik Fleck's epistemology with AD to interpret the discourses about EF-CERN produced by the research participants during the interviews, it is recommended that the thought style would characterize the discursive formation in particle physics, in which both teachers and scientists are enrolled.…”
Section: [] Open the Doors For Us To Get To Know Their Work And For U...mentioning
confidence: 99%
See 1 more Smart Citation
“…Isso é dito explicitamente durante as atividades, de maneira que existe nessa formação uma reprodução ideológica do saber científico e que é percebida pelos professores que participam do curso: Assim, o contexto amplo pode fazer com que o professor se sinta 'privilegiado' por participar da EF--CERN, o que acaba por reforçar o compromisso com a organização, realizando no retorno ao Brasil, atividades de divulgação relacionadas ao CERN. Costa et al (2021) também identificaram que os professores se percebem envolvidos e responsáveis por multiplicarem a vivência no CERN.…”
Section: [] Pessoas Que Trabalham Com Pesquisas Bom Acho Que Vamos Fi...unclassified
“…Como exemplos, destacam-se o trabalho de Londero (2014), que analisou as características da abordagem da física de partículas em sala de aula por professores participantes da EF-CERN e o trabalho de Denardin et al (2019), que mapearam a evolução do perfil acadêmico-profissional de 103 participantes do curso supracitado. Além disso, Costa et al (2021) analisaram os indícios de aprendizagem de um participante da EF-CERN à luz dos focos da aprendizagem do professor pesquisador.…”
Section: Introductionunclassified